Assessing and mapping cultural ecosystem services of an urban forest based on narratives from blog posts - Jeeyoung Kim (Elsevier, 2021)
Although extensive research has been conducted to quantify and map the cultural values of nature and wildlife, there are still many challenges that need to be solved. We propose an approach using blog posts that provide rich narratives and knowledge about place values for assessing cultural ecosystem services (CESs). In this study, blog posts on an urban forest in Korea (Bukhansan) were classified according to different CESs defined by the MA (Millennium Ecosystem Assessment, 2005) through content analysis, while place keywords were quantified and mapped. Consequently, five types of CESs were derived from Bukhansan, whose individual characteristics such as sense of place and aesthetic values in the MA were further subdivided. This relates to the indirect use values that were not sufficiently considered in the existing CES assessment. Indirect use values were found in type 4 and type 5, which accounted for 20% of the CESs in Bukhansan. This is particularly relevant to the location characteristics of Bukhansan, which is adjacent to the city, and its value as an urban forest. Furthermore, semantic relationships of words vectorized by CES type and the occurrence information of place keywords allow for abundant interpretations of people's perceptions and activities. Generally, CESs in mountainous areas, where the scope of activities is limited to traversing nature trails, have similar spatial patterns and physical indicators. However, CESs continue to change with socio-cultural flows, and in this respect, semantic-oriented analysis is more effective in capturing these temporal, spatial, and programmatic features and changes. In conclusion, the use of blog posts for evaluating cultural services can be a compromising alternative to reducing the gap between the quantitative evaluations and the qualitative understanding of the ultimate beneficiaries of the service.